Introducing time-to-educate in a job search model - Sascha O. Becker (Center for Economic Studies and ifo Institute (CESifo), 2005)
Transition patterns from school to work differ considerably across OECD countries. Some countries exhibit high youth unemployment rates, which can be considered an indicator of the difficulty facing young people trying to integrate into the labor market. At the same time, education is a time-consuming process, and enrolment and dropout decisions depend on expected duration of studies, as well as on job prospects with and without completed degrees. One way to model entry into the labor market is by means of job search models, where the job arrival hazard is a key parameter in capturing the ease or difficulty in finding a job. Standard models of job search and education assume that skills can be upgraded instantaneously (and mostly in the form of on-the-job training) at a fixed cost. This paper models education as a time-consuming process, a concept which we call time-to-educate, during which an individual faces the trade-off between continuing education and taking up a job.
Keywords: J31; J64; J41; E24; 330; job search; education; enrollment; dropouts; Arbeitsuche; Berufseinstieg; Bildung; Weiterbildung; Zeitallokation; Theorie